Automatic pan-tilt camera positioning system for motion tracking - Wong, Teck Chang (2004)
In this project, a pan-tilt unit (PTU) which is actuated by two DC motors is used as part of the motion tracking camera system. A camera is mounted on the PTU and the PTU is responsible to move the camera according to the output from the motion tracking algorithm. Accuracy and speed are the two concerns when the PTU is moved because the motion tracking camera is expected to track a single moving object and keep it at the centre of the field of view. A pan-tilt camera positioning system has been developed to meet the characteristics of the motion tracking algorithm and some other hardware constraints. The technique implemented to realize the pan-tilt camera positioning system is an open-loop control called coordinate to motion unit translation. The video frames which are at the size of 256 pixels times 256 pixels are indexed into 392 motion units, which are the points that the camera will centre each time it is being moved. This technique has enabled the manual directivity feature even when the pan-tilt camera is still moving and in the meantime preserves the accuracy of the system. The testing results of the system developed have shown that the motion tracking camera has an accuracy of Â±10 pixels and was able to track a moving object travelling at the speed less than 85 pixels per second.